Penerapan Project-Based Learning Berbasis Kelompok untuk Meningkatkan Hasil Belajar pada Pelajaran Perbankan Dasar - Chatarina Tri Widiastuti (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
The writing of this best practice is intended to describe the distance learning process for basic banking subjects in class X Financial Accounting at SMK Negeri 1 Godean. The data obtained before learning showed that students began to feel bored studying at home and the material was not clear. By applying the group-based Project-Based Learning method in groups, it is hoped that they will work together in learning so that the material becomes clear, and learning outcomes will increase. The learning media used are WhatsApp groups and Google Classroom. Learning is carried out with the stages of analyzing problems, designing and implementing projects, carrying out research, developing project drafts and prototypes, measuring, assessing and improving products, finalizing and publishing products. Quantitative and qualitative data were obtained by survey, observation and performance techniques, with instruments in the form of questionnaires, observation sheets and assessment sheets. From the implementation of the learning, the results of the knowledge value were 47% with very good predicates, 38% good and 15% quite good, skills with 25% very good, 67% good and 8% quite good. good, 29% good, 14% quite good, while 2% is not good. The results of the questionnaire show that the group-based Project-Based Learning model makes the material clearer and improves student learning outcomes. Based on the learning outcomes, the writer recommends the teacher use the group-based Project-Based Learning model to improve student learning outcomes.